the Effect of Problem-Posing and Think-Pair-Share Learning Models on Students’ Mathematical Problem-Solving Skills and Mathematical Communication Skills - Syaiful Rohim; Khoerul Umam (STKIP Singkawang, 2019)
The main purpose of this study was to compare and examine the effectiveness of problem-posing and think-pair-share cooperatives' learning models on mathematical problem-solving skills and mathematical communication skills. This study was experimental research with a quasi-experimental design. The samples of the study were 41 students for classroom experiments and 40 students for classroom control. The instruments employed in this study were pre-test and post-test. The instruments were made in essay forms which design to measure students’ mathematical problem-solving skills. The result of the study showed that problem-posing and think-pair-share are very effective to improve students’ mathematical achievements. However, between the problem-posing and think-pair-share, the think-pair-share is more effective than problem-posing, view from the standards of mathematical problem-solving skills and mathematical communication skills of Junior High School students.